GENOTYPE AND RESISTANCE PATTERNS OF ANTI TUBERCULOSIS TREATMENT (ATT) IN Mycobacterium tuberculosis ISOLATES FROM TUBERCULOSIS CASES WHICH NOT TAKEN ATT - Maria Silvia Merry; Ning Rintiswati; Yanri Wijayanti S (Berkala Ilmiah Kedokteran Duta Wacana, 2016)
Background: Tuberculosis (TB) is still a prominent health problem which need to be controlled worldwide. In Indonesia, the incidences of TB cases in 2011 were 450.000 cases with mortality rate 175 person per day. The emergence of mycobacterium’s resistance against Anti Tuberculosis Treatment (ATT) gives a double burden to prevent the disease. This resistance against ATT is caused by several things, one of which is the nature of mycobacterium, mutations and genotype strain variation. Objective: The aim of this study is to get a description of ATT’s resistance pattern, genotype of M. tuberculosis, and determined the correlation between M. tuberculosis’ genotypes and the resistance pattern against ATT. Methods: The research methods were cross-sectional and analytical descriptions. Samples used in this research were clinical isolates, which were taken from patients who hadn’t received ATT therapy before. Patients were recruited from BP4 (Balai Pengobatan Penyakit Paru = Health Center for Lung’s Diseases) at Minggiran and Kotagede area, for the period of June 2010 - December 2010. Drug susceptibility test for ATT were done for Isoniazid, Rifampicin, Streptomycin, and Ethambutol using LJ’s proportion method. Whereas for genotyping, we were using PCR-based Spoligotyping, with Dra and Drb primers. Data processing for genotypes and resistance pattern were in descriptive form, while the analysis of the ATT resistance and genotypes correlation were using chi square. Results: From 33 samples collected and tested for resistancy, 17 samples (51,52%) were sensitive to INH, RIF, STREP, and ETAMB while 16 samples (48,48%) were resistant to one or more ATT. We found 1 isolate (3.03%) was MDR TB. Genotype patterns description are 30% (10 isolates) were Beijing strain and 70% (23 isolates) were Non Beijing with a variety of EAI, LAM, U, Harleem, T, Manu, and Miscellanous. The chi square’s analysis results are p = 0,034 (p < 0,05), ratio prevalence 2,96 (95 CI 0,26 – 0,57). Conclusion: The result from drug susceptibility test for ATT are 48,48%, resistant to one regimen or more ATT, while sensitivity 51,52%. Beijing strains were predominant strain (30%). There were significant correlation between the patterns of resistance against ATT and genotype patterns, Beijing strains tend to be resistant by 2,96 times greater than non-Beijing strains.